(3eNJUQ aj Yde GdbhGajs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s ((3eMeO Hf CHj GdaVd GdUGFZ s)
(3ChdgG (B:s
(3gPG Yde GdbhGai eNJUQkG bhdg HfjJ GdOjGQ eMdgG abGegG aGdbGajI YfOg ef GdbGa Edi BNQ GdHjJ s
(3BNQgG (B:s
(3hcPdc ENJdGa GdJhLjg cbhdg hbGJe GdCYeGb hNGhi GdeNJQb Je GdeNJUQ HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3CdaI ddCejQ CHj GdaVd YHjO Gddg CMeO GdejcGdis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1438s
Keywords: (3GdCOHs